Henry-Gronwall Integral Inequalities with “Maxima” and Their Applications to Fractional Differential Equations - Phollakrit Thiramanus; Jessada Tariboon; Sotiris K. Ntouyas (Abstract and Applied Analysis)
Some new weakly singular Henry-Gronwall type integral inequalities with “maxima” are established in this paper. Applications to Caputo fractional differential equations with “maxima” are also presented.